The Establishment and Development of Confucius Institute - Bin, Zhang (Lingua Cultura, 2007)
Confucius Institute has been established in the global range. This is a brand of Chinese culture initiatives, as well as the inevitable result of the international "Chinese craze" and also the strong support for the international promotion of the Chinese .Confucius Institute for Teaching Chinese as a foreign language to the main teaching content, adopts a flexible and diverse school running management. Though this initiative there will be a wide-spread Chinese civilization, the promotion of cultural exchanges between China and foreign countries and finally will display the style and image of the Orient big country. This is very significant as to accelerate the development of overseas Chinese education and also lets the world know more about China in order to be closer to China which will be a far-reaching significance.